If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + 3q = 60 Solving 2p + 3q = 60 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-3q' to each side of the equation. 2p + 3q + -3q = 60 + -3q Combine like terms: 3q + -3q = 0 2p + 0 = 60 + -3q 2p = 60 + -3q Divide each side by '2'. p = 30 + -1.5q Simplifying p = 30 + -1.5q
| 2x+10=110+x | | k=20+3k | | 4j=63-3j | | 6d-3=-d+46 | | 2b-8=-4b+34 | | 2d+10=-d+22 | | 30n-9=3(6n+9) | | 3(4x-3)=3x+36 | | 8n=54+2n | | 5j-9=j+3 | | 6(x-4)+7=19 | | 2x-20=7x+4 | | 26=-4+10c | | ax^4+bx^3+cx^2=0 | | 15p=-44-p^2 | | x*94=1000-248 | | 5046/3=420,5*x | | 40=2(x+6) | | Y/x=x/a | | 3t*5w= | | d-3/7=9 | | d-3/7 | | 6(d+7)-3=57 | | 4+55=44x+16 | | 2(3a+4)=40 | | 1+2x=-4+23x | | 4x+7=91-10x | | 7+5=-17+x | | 4r+6=2r+6 | | y=3(2.2)-7 | | 6(x-1)=-3(x-1) | | 5a+9whena=3 |